Bioprospecção de microrganismos de solos do bioma floresta com araucárias e aplicação de consórcios em mudas de jabuticabeira - Oliveira, Paula Juliane Barbosa de (2023)
The application of microorganisms to plants has had positive effects on crop productivity and it has become an alternative for reducing chemical products in the soil. Given the significant effects on agronomic crops, it is necessary to test on other species, such as native fruit trees. Therefore, the objective of this work was to detect species of cultivable microorganisms present in the soils of the Araucária Forest Biome and analyze their potential and effect on the growth of jabuticaba tree seedlings. To carry out this study, soil samples were collected from four remaining forest sites with the presence or absence of native jabuticaba trees (Plinia sp.), located in the Southwest Region of Paraná. After collecting the soil, the microorganisms were isolated and identified by molecular analysis and tested for their capacity in enzyme and IAA production, P solubilization and compatibility and antagonism tests. The isolates were tested individually in seeds and in consortia applying them to jabuticaba tree seedlings. The work was carried out at the Federal Technological University of Paraná and Federal University of Viçosa. The results obtained regarding bioprospecting at the collection sites showed the existence of little diversity among the species of cultivable microorganisms. Of the bacterial species bioprospected, the most predominant genus was Bacillus sp. and for fungi it was Trichoderma sp. Regarding enzyme production tests for amylase, cellulase and protease, bacterial and fungal isolates showed positive results. In the production of indole acetic acid (IAA), only isolates I3 and I17 were able to synthesize it. In P solubilization, only one isolate (I49) showed such capacity. Regarding the inoculation of consortia in jabuticaba tree seedlings, growth was not influenced after 30 days of evaluation. It was concluded that it is necessary to carry out more evaluations for a longer period of time, observing whether there will be a possible difference in these seedlings.